FAKTOR-FAKTOR ANTESEDEN PENENTU KEPUASAN PASIEN DI PUSKESMAS MLATI II - Hermawan, Budi; Sukardi, Sukardi (Universitas Ahmad Dahlan, 2015)
The study entitled “Antecedent Factors Determining Patient SatisfactionIn Mlati II Health Center